Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1894)
Demorest's Family Magazine, May 1894 -- Russian Home Industries -- A Remarkable Portrait Album -- Our Baby Prize -- The Transformation of the Ugly Club -- A Peace Offering -- Advice to Young Writers -- The Writer and the Editor -- History as a Field For Beginners -- The Chances for Poets -- Entering Literature Without A College Education -- Advice to Girl Writers -- The Road to Fame or Fortune: How to Become Successful Professional Women -- Farmer Bradford's Shay -- Some Acclimated Japanese Fruits -- A Fortune by Palmistry -- Society Fads -- The Widow's Match -- Plants for Cemetery Use -- Our Girls -- Home Art and Home Comfort: Venetian Bent Iron Work -- The World's Progress.
New York Illustrated News
Mme Demorest's Mirror of Fashions
Digitized from original print., Valdosta State University Archives and Special Collections, October 20, 2016. Pages 443 and 444 are missing from the physical issue.
Keywords: Demorest's Family Magazine; Dressmaking; Needlework; Illustrated Periodicals; Periodicals; Catalogue; Children; Travel; Women; Women's History; Social History; United States; 1800s; 19th Century; Fashion; Homemaking; Magazine